Reliability and validity of the Thai version of the health of the Nation Outcome Scales (HoNOS) - Bupawan Phuaphanprasert (2018)
Background: Measurement in psychiatric services is important for the development of a psychiatric tool for budget allocation. Objective: To translate the Health of the Nation Outcome Scales (HoNOS) into Thai and to assess its psychometric properties. Material and Method: The HoNOS was translated into Thai, by using the standard of "forward-backward" translation procedure. Two psychiatric nurses interviewed subjects together but independently rated their scores. The subjects were 23 acute inpatients and 23 sub-acute inpatients. The reliability and validity was assessed. Results: The Cronbach's alpha coefficient of the Thai HoNOS was 0.68. It had a high correlation (r > 0.80) with the Brief Psychiatric Rating Scale (BPRS), the Global Assessment of Functioning (GAF) and the Clinical Global Impression (CGI). It suggested high concurrent validity. It had a satisfactory power (p < 0.05) in discriminating overall clinical outcomes between acute and sub-acute psychiatric inpatients. Conclusion: The Thai HoNOS fulfils the requirements of a psychiatric outcome scale for routine use in inpatient service.